2005
DOI: 10.1051/rnd:2005022
|View full text |Cite
|
Sign up to set email alerts
|

An astonishing journey into reproductive genetics since the 1950’s

Abstract: -Training in genetics in Edinburgh in the 1950s led to a PhD on the developmental biology of mouse embryos with unusual chromosomal complements. Fundamental aspects of reproduction under study included ovulation induction, oocyte maturation and embryonic growth to blastocysts. It led to the introduction of embryo stem cells, preimplantation genetic diagnosis, the exact timing of human oocyte maturation in vitro and studies on fertilising human eggs in vitro to alleviate human infertility. My work was helped by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Mouse embryos are frequently used in the development of ART that will ultimately be applied to human embryos. Notably, the mouse has played an important role in the development of IVF [33], the development of culture systems [10] and embryo cryopreservation [34], and the reader is referred to these reviews for more detailed discussion of these areas. Mouse embryos continue to play a role in the development of new assisted reproductive techniques; once demonstrated to be safe and effective in the mouse, these techniques can be applied to embryos from other species, a strategy that is recommended but not always followed [35].…”
Section: Assisted Reproductive Technologiesmentioning
confidence: 99%
“…Mouse embryos are frequently used in the development of ART that will ultimately be applied to human embryos. Notably, the mouse has played an important role in the development of IVF [33], the development of culture systems [10] and embryo cryopreservation [34], and the reader is referred to these reviews for more detailed discussion of these areas. Mouse embryos continue to play a role in the development of new assisted reproductive techniques; once demonstrated to be safe and effective in the mouse, these techniques can be applied to embryos from other species, a strategy that is recommended but not always followed [35].…”
Section: Assisted Reproductive Technologiesmentioning
confidence: 99%
“…Edwards saw that to understand development involved engaging in an interdisciplinary mix, not just of embryology and reproduction, the conventional view at the time, but also of genetics. Given the scientific and social emphasis on genetics over the last 40 or so years, it is important to understand how advanced this view was in the 1950s, when genetic knowledge was still rudimentary and largely alien to the established developmental and reproductive biologists of the day, as Edwards himself was later to recall (Edwards, 2005). For example, it was in the 1950s that DNA was established as the molecular carrier of genetic information (Watson and Crick, 1953a,b; Franklin and Gosling, 1953; Wilkins et al, 1953), that it was first demonstrated that each cell of the body carried a full set of DNA/genes (Gurdon, 1962a,b; Gurdon et al, 1958) and that genes were selectively expressed as mRNA to generate different cell phenotypes (Weinberg, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Paul was then the acknowledged master of tissue culture in the UK and had got wind of some experiments that Edwards had been doing on the side at NIMR attempting to generate stem cells from rabbit embryo cultures (Edwards, 2005). The objective of this strategy was to use these stem cells to study early developmental mechanisms, either in vitro , or in vivo after their incorporation into embryos.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…94 Edwards believed this development would be useful in 'certain clinical and scientific uses for human eggs fertilized by this procedure'. In 1969, Robert Edwards and his colleagues reported successful in vitro maturation and fertilization of human oocytes.…”
Section: Reproductive History and Development From An Orthodox Medicamentioning
confidence: 99%